Multi-unit floating alginate system: Effect of additives on ciprofloxacin release - Srinatha A.; Pandit J.K. (My University, 2025)
In an attempt to fabricate floating beads of ciprofloxacin, drugloaded alginate beads were prepared by simultaneous external and internal gelation. The effect of blending of alginate with gellan, hydroxypropyl methylcellulose, starch, and chitosan on the bead properties were evaluated. Beads were spherical with incorporation efficiency in the range of 52.81 ± 2.64 to 78.95 ± 1.92%. Beads exhibited buoyancy over a period of 7-24 hr based on the formulation variables. In vitro release of ciprofloxacin from the alginate beads in simulated gastric fluid (SGF) (0.1 N HCl, pH 1.2), was influenced significantly (p < 0.001) by the properties and concentration of additives. Among the polymers incorporated into alginate beads. Hydroxy propyl methylcellulose (HPMC) provided an extended release over 7 hr. The drug release predominately followed Higuchi's square root model. Copyright © Informa UK, Ltd.